Lateral and Vertical Graphene/Hexagonal Boron Nitride Heterostructures Grown by Molecular Beam Epitaxy - Thomas, James C. (2021)
This thesis discusses the investigation of graphene/ hexagonal Boron Nitride (hBN)heterostructures grown by Sergei V. Novikov and Tin S. Cheng using molecular beam epitaxy (MBE), with a focus on measurements recorded using atomic force microscopy (AFM), in particular conductive AFM (CAFM). MBE is a relatively uncommon deposition technique for graphene growth that offers a route to scaleable high quality material. In this thesis three different carbon sources have been used to grow strained graphene samples at high temperature (up to ~ 1700 degC) on exfoliated hBN flakes. These samples have been subsequently analysed using a range of techniques including AFM, CAFM, lateral force microscopy (LFM), Raman spectroscopy, and angle resolved photoemission spectroscopy (ARPES). A particular focus is placed on the recorded strain of these structures, measured with the aid of the hexagonal graphene/hBN moiré superlattice pattern formed at the interface of the stacked 2D structure. In order to carry out the CAFM measurements shown, electrical contacting procedures have been developed as part of this work in order to measure electrically isolated graphene/ hBN regions. The most prominent of these methods has been the deposition of a conductive silver nanowire networking layer.